Relationship of milk expected progeny differences (EPD's)to milk production and calf weaning weight - Marston, T.T.; Simms, D.D.; Schalles, R.R.; Zoellner, K.O.; Clarke, L.S.; Fink, G.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Spring-calving Angus (n=37) and Simmental (n=28) cows were used to evaluate the relationship between milk expected progeny difference (EPD), milk production, total milk energy, and weaning weight. There were positive correlations between milk EPD’s and milk produced during lactation, total milk energy per lactation, and calf weaning weight. On average, a 1 lb increase in milk EPD predicted a 1.8 lb increase in calf weaning weight and an increase of 56.6 (Angus) and 70.2 (Simmental) lb in total milk per lactation. Our results suggest that producers can use milk EPD’s as selection tools to influence the milk production of their cows and subsequent weaning weights of their calves.
Keywords: Beef; expected progeny differences (EPD's); Milk production; Calf weaning weight